2017
DOI: 10.1037/ccp0000148
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of motivational interviewing plus feedback for soldiers with untreated alcohol abuse.

Abstract: This novel adaptation of MIF shows promise for decreasing drinking and alcohol dependence among this high-risk sample of non-treatment-seeking soldiers and may complement existing AUD services already provided by the Army. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 46 publications
0
41
0
Order By: Relevance
“…The findings showed that the intervention resulted in significantly fewer drinks per week and lower rates of alcohol dependence diagnosis. 42 …”
Section: Introductionmentioning
confidence: 99%
“…The findings showed that the intervention resulted in significantly fewer drinks per week and lower rates of alcohol dependence diagnosis. 42 …”
Section: Introductionmentioning
confidence: 99%
“…37,38 Similar to our study, Walker et al found that repeated assessment for alcohol abuse followed by a single session of telephone-delivered MI versus psychoeducation (no MI) were both associated with increased treatmentseeking in soldiers with untreated alcohol abuse, pinpointing repeated assessment as a key ingredient. 39 The between-group descriptive analyses for the secondary outcomes demonstrated that veteran peer motivational coaching resulted in improved MH symptoms, reduced cannabis use, improved quality of life scores, and encouraged self-care activities compared to controls as observed in another study. 31 This finding may be explained by the fact that "partnership" was the highest of the peers' MITI global ratings.…”
Section: Discussionmentioning
confidence: 65%
“…These findings align with studies which have demonstrated that assessment of substance use alone is associated with significant reductions in use, known as “assessment reactivity.” 37 , 38 Similar to our study, Walker et al found that repeated assessment for alcohol abuse followed by a single session of telephone‐delivered MI versus psychoeducation (no MI) were both associated with increased treatment‐seeking in soldiers with untreated alcohol abuse, pinpointing repeated assessment as a key ingredient. 39 …”
Section: Discussionmentioning
confidence: 99%
“…By contrast, video and telephone‐based motivational interviewing and mobile health apps to provide behavioural prompts and feedback have been used successfully to change behaviours in other populations. These populations include those with diabetes and long‐term conditions that require sustained adherence behaviours . The use of technology to support behaviours is of particular relevance when considering that the cognitive abilities of those who have diabetic foot ulceration are reduced .…”
Section: Discussionmentioning
confidence: 99%
“…These populations include those with diabetes and long-term conditions that require sustained adherence behaviours. [47][48][49][50] The use of technology to support behaviours is of particular relevance when considering that the cognitive abilities of those who have diabetic foot ulceration are reduced. 42 Mobile devices can play a significant role in prompting and motivating behavioural change where there is a reduced cognitive capacity and a decreased ability to concentrate.…”
Section: By Contrast Video and Telephone-based Motivational Interviementioning
confidence: 99%